Consumer Behavior in The Digital Age: A Study Of Online Shopping Trends - Jalaja, S.; Thakur, Reena; Saritha, M.; Anupama, P. (International Journal of Psychosocial Rehabilitation, 2020)
The digital age has significantly transformed consumer behavior, particularly in the realm of online shopping. This study explores the key trends driving consumer behavior in the digital marketplace, examining factors such as convenience, personalization, and the role of social media. The rapid growth of e-commerce has reshaped traditional shopping habits, influenced by technological advancements like artificial intelligence, augmented reality, and mobile commerce. Additionally, the research highlights the changing decision-making process, including the rise of impulse buying and the influence of social media. While online shopping offers numerous advantages, challenges such as data privacy, competition, and managing returns persist. This study aims to provide insights into the evolving dynamics of consumer behavior, offering strategic perspectives for businesses to adapt in this competitive digital landscape.